Exploring the contributions of the supplementary eye field to subliminal inhibition using double‐pulse transcranial magnetic stimulation. Issue 1 (9th September 2016) - Chiau, Hui‐Yan; Muggleton, Neil G.; Juan, Chi‐Hung
Abstract: It is widely accepted that the supplementary eye fields (SEF) are involved in the control of voluntary eye movements. However, recent evidence suggests that SEF may also be important for unconscious and involuntary motor processes. Indeed, Sumner et al. ([2007]: Neuron 54:697–711) showed that patients with micro‐lesions of the SEF demonstrated an absence of subliminal inhibition as evoked by masked‐prime stimuli. Here, we used double‐pulse transcranial magnetic stimulation (TMS) in healthy volunteers to investigate the role of SEF in subliminal priming. We applied double‐pulse TMS at two time windows in a masked‐prime task: the first during an early phase, 20–70 ms after the onset of the mask but before target presentation, during which subliminal inhibition is present; and the second during a late phase, 20–70 ms after target onset, during which the saccade is being prepared. We found no effect of TMS with the early time window of stimulation, whereas a reduction in the benefit of an incompatible subliminal prime stimulus was found when SEF TMS was applied at the late time window. These findings suggest that there is a role for SEF related to the effects of subliminal primes on eye movements, but the results do not support a role in inhibiting the primed tendency. Hum Brain Mapp 38:339–351, 2017 . © 2016 Wiley Periodicals, Inc.